A Single-Center, Retrospective Cohort Study Evaluating the Use of Probiotics for the Prevention of Hospital-Onset Clostridioides difficile Infection in Hospitalized Patients Receiving Intravenous Antibiotics. (February 2023) - Shah, Punit Jitendra; Halawi, Hala; Kay, Jessica; Akogun, Adanma; Wise, Silvia; Aly, Sarfraz; Daoura, Nicolas; Putney, David
Background: Exposure to antimicrobials is a known risk factor for Clostridioides difficile infection (CDI). Antimicrobials cause collateral damage by disrupting the natural intestinal microbiota allowing for C. difficile to thrive and production of C. difficile toxins. Probiotics could modulate the onset and course of CDI. However, the data on probiotics for the prevention of CDI is conflicting. Objective: To evaluate the rates of hospital-onset Clostridioides difficile infection (HO-CDI) among patients who received intravenous (IV) antibiotics plus probiotics versus IV antibiotics alone. Design: Retrospective, single-center cohort study. Methods: We included adult patients that received at least 1 dose of IV antibiotics and had a hospital length of stay of at least 3 days between August 2017 and July 2020. Patients were separated into 2 cohorts, either receipt of probiotics or non-receipt of probiotics. Patients with positive C. difficile toxin test prior to antibiotic therapy, or receipt of only C. difficile active treatment were excluded. The primary outcome was incidence of HO-CDI in patients who received IV antibiotics plus probiotics compared to those that received IV antibiotics alone. Logistic regression was performed to account for confounding variables. Results: We identified 17 598 patients that received IV antibiotics alone and 2659 patients received IV antibiotics plus probiotics. HO-CDI occurred in 46 (0.26%) of those that received antibiotics alone compared to 5 (0.19%) of those that received probiotics with IV antibiotics (OR 0.72, 95% CI 0.28-1.81). ICU admission (OR 1.81, 95% CI 1.02-3.19) and history of CDI (OR 3.37, 95% CI 1.07-10.97) in the past 12 months were associated with a higher incidence of HO-CDI. Conclusion: The addition of probiotics did not reduce the incidence of HO-CDI among inpatients receiving IV antibiotics.